Usability Evaluation In Ruang Guru Applications Using User Experience Questionnaire (UEQ): Usability Evaluation In Ruang Guru Applications Using User Experience Questionnaire (UEQ) - Sepyan Purnama Kristanto; Lutfi Hakim; Francisca Hariyati C (Jurnal Mantik, 2020)
Mobile learning is a form of reconstruction effort for past learning models to digital. Easy access and excellent performance is one aspect of mobile learning support is acceptable and running smoothly. The ruang guru application used as an object in this research was chosen based on the review of the best mobile learning app version of Playstore Indonesia with a download of ± 10 million. Usability is one of the essential aspects to note in the development of an application so that the developed application has a good experience from the user. User Experience Questionnaire focuses on the aspect of user satisfaction measured using Quisioner with the standard Don Foundation. The measurements carried out in this study used 100 active users of the ruang guru application, using the Quisioner that was disseminated randomly in the school stay. The results of measurements that have done resulted in an effectiveness score of 59.38, an efficiency of 65.36, and a satisfaction score of 62.52.